A First Ceramic Chronology for the Late Islamic Arabian Gulf. (16th July 2015) - Power, Timothy
Abstract : Islamic archaeology in the Arabian Gulf has grown tremendously in recent years. However, a ceramic chronology for the Late Islamic Arabian Gulf has not yet been put forward. The present paper constitutes a first attempt at a refined periodization based on the occupational sequence of al-Ain, UAE. The study is based on the typological quantification of sherds from stratified excavations undertaken by the Tourism and Culture Authority of Abu Dhabi. It is broadly based on the methodology developed by Derek Kennet in his much-cited "Sasanian and Islamic Pottery from Ras al-Khaimah" (2004). The 13, 649-sherd assemblage has been divided into six periods of thirty to seventy years spanning the later seventeenth to mid-twentieth centuries. The al-Ain assemblage is compared to published ceramics from contemporary sites in the Gulf region and further compared to relevant historical sources to draw out the wider implications of the findings. The present study constitutes an interim report and full publication of ceramics from al-Ain will appear in a pottery handbook currently in preparation.